PJKR FKIP UPR Student Perception of Practitioner Performance in Teaching Practitioner Program 3 in 2023 - Harvianto, Yudo (JUPE : Jurnal Pendidikan Mandala, 2023)
Education has a very important role for the progress of a nation. In life, education has become a basic need for everyone. Therefore, various  efforts in various programs to make education better and advanced are always carried out by the central and regional governments. As an ideal in creating a quality community life, universities have a very important and strategic role. To produce quality scholars, professional and competent educators are needed in carrying out their duties. One of the central government programs through the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia in achieving the quality of quality undergraduate graduates is by holding a Teaching Practitioner program. The Physical Education, Health and Recreation Study Program, Faculty of Teacher Training and Education, University of Palangka Raya is one of the study programs that runs the program. There are several professional practitioners who have taught in several courses. The purpose of this study is to describe the Perception of PJKR FKIP UPR Students on Practitioner Performance in the Teaching Practitioner Program 3 in 2023. In this study, descriptive quantitative methods were used. A total of 114 students of PJKR FKIP UPR as subjects in this study. The data collection technique used in this study was a questionnaire in the form of indirect communication through google form. The conclusion of this study is that in the learning process, practitioners have created a fun learning process that has an impact on increasing student interest in learning. In the learning process, practitioners have also given rewards in the form of praise to students who have been considered successful. Practitioners have also provided maximum guidance to students during the learning process, thus having an impact on increasing student learning motivation. Reprimands are also given by practitioners to students if they do actions that are considered not good, so that students can correct mistakes that have been made during the learning process.